Removal of malachite green dye using sulphuric acid treated durian leaves adsorbent / Fazrizal Dolkafri - Dolkafri, Fazrizal (2016)
Durian leaves was treated with sulphuric acid and its performance in the removal of malachite green from aqueous solution was evaluated. This study was performed in a batch adsorption system. The effect of several important parameters which can affect adsorption capacity such as pH, dosage, initial concentration and contact time were also studied. The optimum pH for malachite green adsorption was 10. Even at low adsorbent dosage of 0.02 g, the adsorption has reached 93% of malachite green could be removed. The adsorption capacity was also dependent on malachite green concentration and contact time which only 30 min at concentration 10 mg/L of malachite green to reach equilbrium. Two isothenn model : Langmuir and Freundlich were used to analyze malachite green ions adsorption process and from the equilibrium data presented better fitting to Langmuir isotherm model which is based on assumption that adsorption occur at specific homogenous sites on the adsorbent. Based on Langmuir model, the maximum adsorption of malachite green ions was 294.12 mg/g. Two kinetic models; pseudo-first order and pseudo-second order were used to analyze malachite green ions adsorption process and the results shows that pseudo-second order was fitted well and chemical reaction could be the rate determining steps.